2016
DOI: 10.1002/ccd.26347
|View full text |Cite
|
Sign up to set email alerts
|

The outcomes of transcatheter aortic valve replacement in a cohort of patients with end‐stage renal disease

Abstract: Objectives: To examine whether transcatheter aortic valve replacement (TAVR) is a safe and effective treatment option for aortic stenosis in patients with end-stage renal disease (ESRD). Background: Patients with ESRD undergoing surgical aortic valve replacement have an operative mortality approaching 20% and a 10-year survival of approximately 12%. We investigated whether TAVR is a more reasonable option. Methods: This is a multicenter, retrospective study of all patients with ESRD who underwent TAVR in 8 ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…[15][16][17][18] However, patients with CKD and CLD undergoing TAVR are at increased risk of procedural complications, mortality, and rehospitalization when compared with those without these conditions. 17,18 In addition to patient comorbidities, TA-TAVR and AKI were also identified as independent predictors of 30-day readmission. TA-TAVR is an accepted approach in patients in whom vascular anatomy or severe PVD precludes safe transfemoral (TF) access.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] However, patients with CKD and CLD undergoing TAVR are at increased risk of procedural complications, mortality, and rehospitalization when compared with those without these conditions. 17,18 In addition to patient comorbidities, TA-TAVR and AKI were also identified as independent predictors of 30-day readmission. TA-TAVR is an accepted approach in patients in whom vascular anatomy or severe PVD precludes safe transfemoral (TF) access.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular diseases are highly prevalent among dialysis patients, with aortic stenosis being the most common valvular disease affecting them 1820 . The management of aortic stenosis in dialysis patients is becoming an increasingly relevant topic for two reasons: (1) The prevalence, risk profile and longevity of patients on dialysis have changed in the past two decades 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Several small studies assessed the outcomes of TAVR in dialysis patients compared to those with normal renal function and found maintenance dialysis to be an independent predictor of in-hospital and long-term mortality 18, 2429 . Dialysis status has now become a standard element in the TAVR risk prediction tool derived from large-scale data available in the ACC/TVT registry 30, 31 .…”
Section: Discussionmentioning
confidence: 99%
“…127 Operative mortality was 14%, similar to 19% in ESRD patients getting a SAVR. and mortality, however, TAVR seems to be at least as safe and effective as SAVR in patients undergoing AV repair.…”
mentioning
confidence: 85%
“…studies on contrast load or osmolality, timing of contrast studies, volume expansion or holding diuretic strategies, use of bicarbonate solutions or NAC. Szerlip et al 127 performed a large multicenter retrospective study on the outcomes of TAVR in a national cohort of ESRD patients and found that ESRD patients who underwent TAVR were at high-risk for mortality (6-month mortality was 26%) with the rest of outcomes not substantially better than SAVR.…”
mentioning
confidence: 99%